National Artificial Intelligence Policy - José Fernando Valencia Grajales; Mayda Soraya Marín Galeano; Luis Felipe Ortiz-Clavijo (Ratio Juris)
This analysis examines Colombia’s National Artificial Intelligence Policy and its evolution towards a specific framework for the responsible adoption of AI. Based on official documents, the policy is shown to have transitioned from Big Data exploitation strategies (CONPES 3920) to a comprehensive program emphasizing ethics, governance, infrastructure, R&D&I, talent development, and risk mitigation. Two national policies (CONPES 3975 from 2019 and CONPES 4144 from 2025) are compared, highlighting that the latter significantly increases investment, extends the planning horizon to 2030, and establishes clear mechanisms to ensure transparency, accountability, and social benefits. The proposal underscores the importance of aligning governmental initiatives with international standards and promoting digital transformation as a driver of competitiveness and inclusive development.